Developing Mobile Applications for Emergency Services - Mariam Soliman Hamid; Shaimaa Foad Senary (المجلة الدولية للحاسبات والمعلوماتية, 2023)
Mobile phone applications have gained tremendous attention over the past few years due to an increase in mobile phone downloads and revenue. However, the more applications are produced, the more applications fail. Mobile applications statistics indicate that the main drivers of application failure include high consumer/consumer expectations, inadequate marketing efforts, and technical problems resulting from developers failing to use appropriate methodologies. Some of these applications may not be important, but failures in mobile applications used by civil protection to provide important information in times of crisis, such as location-based services, are not acceptable in any way. This paper provides a framework that uses the Scrum methodology to develop a mobile application to alert citizens to risks and manage the team to improve collaboration, coordination, and communication between the team (s) to get quick feedback from users to address rapid developments in context and achieve desired goals.